CHLORHEXIDINE AS AN ADJUVANT IN ULTRASOUND SCALING - Cristian Marin; Vlad Popescu; Radu Costea (Romanian Society of Oral Rehabilitation, 2014)
In this study the authors have studied the results of using Chlorhexidine during preventive strategies. It evaluates the clinical results after conventional methods of professional cleaning by ultrasonic scaling, brushing, sanding (air flow) using Chlorhexidine (CHX). The study was conducted on a total of 328 Subjects equally divided in one reference group and one study group. The purpose is to establish a risk assessment strategy and apply preventive measures to each individual according to the diagnosis illness preponderance. The result is a better wellness status after the use of Chlorhexidine during the ultrasound scaling procedures.